2005
DOI: 10.3354/dao064135
|View full text |Cite
|
Sign up to set email alerts
|

SSU rDNA analysis of Kudoa rosenbuschi (Myxosporea) from the Argentinean hake Merluccius hubbsi

Abstract: The cloning and sequencing of the small subunit (SSU) ribosomal DNA gene from Kudoa rosenbuschi (myxosporean species associated with post-mortem myoliquefaction process in the Argentinean hake Merluccius hubbsi) is reported. The SSU rDNA was found to contain 1740 bp with a single polymorphic site with either a C or T at position 221. The sequence data obtained in this study and those known sequences of Kudoa species deposited in the GenBank were all analyzed to construct a phylogenetic tree. Nucleotide sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…However, the resemblance of K. alliaria spores (Fig. 1) to those of K. rosenbuschi provided in figures by Sardella (1988) and Abollo et al (2005) is striking. This is not to say that these authors made a misidentification, but simply illustrates some of the morphological similarities between these parasites.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…However, the resemblance of K. alliaria spores (Fig. 1) to those of K. rosenbuschi provided in figures by Sardella (1988) and Abollo et al (2005) is striking. This is not to say that these authors made a misidentification, but simply illustrates some of the morphological similarities between these parasites.…”
Section: Resultsmentioning
confidence: 80%
“…This sequence was compared to those of other related Kudoa species as determined from previous analyses (Blaylock et al 2004, Abollo et al 2005, Diamant et al 2005) and using the basic local alignment search tool (BLAST) on GenBank (Altschul et al 1990). Sequences were aligned with Clustal X (Thompson et al 1997) and pairwise sequence similarities were generated with BioEdit version 7.0.5 (Hall 1999).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that there are many Kudoa spp. and that they infect both freshwater fish and sea fish (Abollo et al 2005); however, only K. septempunctata has been proposed to be detrimental to human health. One characteristic of the foodborne sickness caused by K. septempunctata is a rapid recovery, and the disease has a good prognosis ).…”
Section: Introductionmentioning
confidence: 99%